English Scholarly Publishing Activities in the Industrial Revolution 4.0: What, Why, and How? - Dedi Turmudi (English Language Teaching Educational Journal, 2020)
Â The presence of the Industrial Revolution (IR) 4.0 has inevitably affected the way how scholars proceed to write. Thus, activities intended to yield a piece of scientific writing facilitated by the obtainability and accessibility of internet browsing is called scholarly publishing. Since English has indisputably become the language of international scholarship and research, it is urgent to have the skill in writing scientific articles benefitting the support from IR 4.0 principles. What is going on with academics and what should they do dealing with the IR 4.0 pertinent to their scholarly writing activities, benefits, and drawbacks. This paper discusses what scholarly publishing in the Industrial Revolution 4.0 and how it supports the process of writing articles for publishing. The purposes of this paper are to explain (1). What are scholarly publishing and industrial revolution? (2). Why is it essential for academics? (3) How does writing scholarly publication in Industrial Revolution 4.0 work? Writing the scholarly publication in English has become obligatory for Teacher-Educator Authors (TEAs) and undergraduate students to doctoral students in Indonesia. The study was a descriptive qualitative library to build a conceptual paper for the purpose of a further study. The method was by reviewing any related kinds of literature to provide sufficient arguments for the three research questions. The outcome is several claims, arguments, and evidence gambits for any author to consider. Theoretically, the IR 4.0 principles have significantly eased the flexibility of the process, the quality, and the credibility of research outputs.